2013
DOI: 10.1063/1.4776710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion temperature on ion-acoustic solitary waves in a magnetized plasma in presence of superthermal electrons

Abstract: Obliquely propagating ion-acoustic soliatry waves are examined in a magnetized plasma composed of kappa distributed electrons and fluid ions with finite temperature. The Sagdeev potential approach is used to study the properties of finite amplitude solitary waves. Using a quasi-neutrality condition, it is possible to reduce the set of equations to a single equation (energy integral equation), which describes the evolution of ion-acoustic solitary waves in magnetized plasmas. The temperature of warm ions affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…Elaborating on those earlier works, we have investigated the effect of superthermality on the propagation of ion acoustic waves in the presence of ion temperature anisotropy. Our results are in agreement with all known previous works [34][35][36] in the appropriate limiting cases. We observe that lower values of j lead to an increase in the amplitude of the soliton, which is more localized in space and also steeper, as shown in Figure 2.…”
Section: A Effect Of Superthermalitysupporting
confidence: 83%
See 1 more Smart Citation
“…Elaborating on those earlier works, we have investigated the effect of superthermality on the propagation of ion acoustic waves in the presence of ion temperature anisotropy. Our results are in agreement with all known previous works [34][35][36] in the appropriate limiting cases. We observe that lower values of j lead to an increase in the amplitude of the soliton, which is more localized in space and also steeper, as shown in Figure 2.…”
Section: A Effect Of Superthermalitysupporting
confidence: 83%
“…It has been shown that smaller values of the superthermality parameter j (i.e., larger deviation from Maxwellian equilibrium) enhances solitary waves. Recently, Singh et al 35 confirmed the same qualitative result in the warm ion fluid model. Elaborating on those earlier works, we have investigated the effect of superthermality on the propagation of ion acoustic waves in the presence of ion temperature anisotropy.…”
Section: A Effect Of Superthermalitysupporting
confidence: 72%
“…8,9 When the amplitudes of Alfven waves are sufficiently large, one cannot neglect nonlinearities. The latter contribute to the localization of waves and lead to different types of nonlinear structures, such as solitons, [10][11][12][13][14][15][16][17] shocks, [18][19][20][21][22] vortices, 23 etc.…”
Section: Introductionmentioning
confidence: 99%
“…In scientific and engineering fields, nonlinear evolution equations have been studied in wide applications, such as in the nonlinear optics [1][2][3][4][5][6][7], plasma physics [8,9], fluid mechanics [10,11], textile engineering [12], and wave propagation phenomena [13][14][15][16]. Explicitly, for finding solutions, which including solitons, cnoidal waves, Painlevé waves, Airy waves, Bessel waves, etc., people often take the symmetry reduction approach with nonlocal symmetries with the aid of Darboux transformation, Bäklund transformation, and residual symmetry [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%